MicroRNA-194 inactivates hepatic stellate cells and alleviates liver fibrosis by inhibiting AKT2 - Wu, Jun-Cheng (World J Gastroenterol, 2019)
BACKGROUND: Activation of hepatic stellate cells (HSCs) is a pivotal event in the onset and progression of liver fibrosis. Loss of microRNA-194 (miR-194) has been reported in activated HSCs, but the actual role of miR-194 in liver fibrosis remains uncertain. AIM: To explore the role and potential mechanism of miR-194-mediated regulation of liver fibrosis in vitro and in vivo. METHODS: The expression of miR-194 was examined in human fibrotic liver tissues, activated HSCs, and a carbon tetrachloride (CCl(4)) mouse model by qPCR. The effects of AKT2 regulation by miR-194 on the activation and proliferation of HSCs were assessed in vitro. For in vivo experiments, we reintroduced miR-194 in mice using a miR-194 agomir to investigate the functions of miR-194 in liver fibrosis. RESULTS: MiR-194 expression was notably lacking in activated HSCs from both humans and mice. Overexpression of miR-194 (OV-miR-194) inhibited α-smooth muscle actin (α-SMA) and type I collagen (Col I) expression and suppressed cell proliferation in HSCs by causing cell cycle arrest in G0/G1 phase. AKT2 was predicted to be a target of miR-194. Notably, the effects of miR-194 knockdown in HSCs were almost blocked by AKT2 deletion, indicating that miR-194 plays a role in HSCs via regulation of AKT2. Finally, miR-194 agomir treatment dramatically ameliorated liver fibrosis in CCl(4)-treated mice. CONCLUSION: We revealed that miR-194 plays a protective role by inhibiting the activation and proliferation of HSCs via AKT2 suppression. Our results further propose miR-194 as a potential therapeutic target for liver fibrosis.